Workshop Pembuatan E-Modul Interaktif Pada MGMP Sejarah Kota Lubuklinggau - Dodik Mulyono; Drajat Friansah; Yeni Asmara (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
Teachers in schools in general have never received training on e-learning using e-modules. Through e-learning, students not only listen to material descriptions from educators but also actively observe, perform, demonstrate, and so on. Teaching materials can be virtualized in various formats so that they are more interesting and more dynamic so that they can motivate students to go further in the learning process. One form of utilization of e-learning is to use interactive e-modules. The purpose of this service is to provide workshops so that teachers can make interactive emodules well. The method used is through 3 (three) stages, namely the preparation stage, the implementation stage and the evaluation stage. The results of this activity are that the participants consist of the achievement of the objectives of community service activities, namely: the achievement of the material delivered, and the teacher's motivation seems to increase to learn to make interactive emodules.